KECEPATAN PENCAPAIAN TARGET ENERGI DAN PROTEIN SERTA HUBUNGANNYA DENGAN PENURUNAN INDEKS MASSA TUBUH DAN LINGKAR LENGAN ATAS PADA PASIEN STROKE - Joriandhita Ramadhan; Hertanto Wahyu Subagio; Enny Probosari (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2022)
Background: Some anthropometrics assessment on risk of malnutrition are by measuring the mid-arm circumference (MAC) and calculating the body mass index (BMI). Objective: To analyze the relationship between days of energy and protein target achievement to the reduction of MAC and BMI in stroke patients in Indonesia. Method: The study design was an observational study with a cross-sectional approach to determine the relationship between days of energy and protein target achievement to the reduction of MAC and BMI. A total of 55 subjects who met the inclusion and exclusion criteria were taken at the Stroke Unit of RSUP Dr. Kariadi Semarang during January-March 2021. MAC measurements and BMI calculations were carried out. Analysis of the relationship between dependent and independent variables using the chi square statistical test. Results: Most of the subjects achieved their energy and protein targets within ≤ 3 days. Days of energy and protein target achievement did not correlate with the reduction in MAC and BMI statistically (p> 0.05), but the research data stated that as a percentage, one third of the subjects who reached the energy and protein targets ≤ 3 days did not experience reduction. Conclusion: All subjects were stroke patients aged 19-59 years where 49 (89,1%) could meet their energy and protein targets within ≤ 3 days and 17 (34,7%) subjects did not experience reduction in MAC and BMI. Keywords: Stroke, MAC, BMI, malnutrition, anthropometry